Natural Acid-Base Indicators as Home-based Experiments: Feasibility, Satisfaction, and Teachers’ Experiences in Secondary Science Blended Instruction - Cerna, Ellen; Cortes, Shayne Fate; Padilla, Kyle Jay; Pepino, Chese Ann; Guion, Janielle Bernice; Gomez, Shane Dae; Taniola, John Vincent; Sumalinog, Kristine; Dinawanao, Charlene; Callanga, Charnel; Sanchez, Joje Mar (FKIP Universitas Lampung, 2023)
Natural Acid-Base Indicators as Home-based Experiments: Feasibility, Satisfaction, and Teachers’ Experiences in Secondary Science Blended Instruction. Objectives: Common plants in the community can be used as acid-base indicators in laboratory experiments for blended learning in Chemistry. With this, the researchers conducted a study on the feasibility of the home-based experiments as well as the satisfaction and experiences of secondary-level teachers. Methods: Through a stratified random sampling from northern, southern, and metro Cebu in Central Visayas, Philippines, 45 teachers performed the experiment, answered the survey questionnaire, and were interviewed about their experiences. Data was collected and analyzed using descriptive and thematic analyses. Findings: The results showed that the home-based experiments were very feasible in terms of independent learning (μ=4.52, SD=0.50), resource availability (μ=4.25, SD=0.43), and safety considerations (μ=4.28, SD=0.68), as well as feasible according to adult supervision (μ=2.48, SD=1.06). Moreover, the experiments produced a very positive experience (μ=4.72, SD=0.40), which can be attributed to resource availability (ρ=0.574, p=0.000) and safety considerations (ρ=0.415, p=0.004). Furthermore, the teachers encountered opportunities, overcame challenges, and proposed improvements to the experiment. Conclusion: The home-based experiments on natural acid-base indicators are very feasible and highly satisfactory. Keywords: acid-based indicators, home-based experiments, secondary chemistry blended instruction.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202334